2001
DOI: 10.1007/s001700170205
|View full text |Cite
|
Sign up to set email alerts
|

Sealing Performance of Gasketed Bolted Flanged Joints: A Fuzzy Decision Support System Approach

Abstract: The paper describes a fuzzy decision support system (FDSS) and its application to the selection of sets of optimal parameters to characterise the gasket sealing performance in gasketed bolted flanged joints. The FDSS of fuzzy logic theory is applied considering the gas pressure, gasket deflection, and leakage rate based on required gasket stress and flange surface roughness. The idea and implementation of the fuzzy decision support system is based on the compositional rules of inference and can be applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…3. An optimum sealing performance depends on the proper contact between the diffuser and the gasket propitiated by a proper design of it [5], and the compressive clamping force applied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3. An optimum sealing performance depends on the proper contact between the diffuser and the gasket propitiated by a proper design of it [5], and the compressive clamping force applied.…”
Section: Introductionmentioning
confidence: 99%
“…2, main components of a weatherproof luminary are the outer cover formed by two elements: a transparent or translucent diffuser (1) and an opaque housing (2); the sealing performance is achieved thanks to locking clips (3); a flexible gasket (5), and the lighting system (4), usually assembled on a metallic tray.…”
Section: Introductionmentioning
confidence: 99%
“…These damages are real problems for aircraft manufacturers as well as for airline companies such as lengthening of delivery times, aircraft crashes in extreme cases, etc. [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Improper preload can degrade the behavior and life span of the joint and lead to joint problems, such as material failure, fastener loosening, joint separation, leakage, rattle, and fatigue failure [2] to [4]. It has been reported that up to 90% of bolted joint failures are caused by incorrect initial bolt tightening [5]. In the assembly of miniature precision equipment, performance degradation can be attributed to nonuniform stress, which is caused by the scatter of bolts preload.…”
Section: Introductionmentioning
confidence: 99%